Teaching methods of arithmetics basics in different countries - Žilinskienė, Inga; Dagienė, Valentina (Lietuvos matematikos rinkinys, 2008)
This paper deals with main teaching methods of arithmetics – addition, subtraction, multiplication, and division in different countries: USA, Israel, Germany, Austria, Japan, Egypt, and the Netherlands. Methods of teaching arithmetics basics and methodology of its application have been discussed. The paper reports on a survey conducted on methods of teaching arithmetics actions at the introductory level. It presents some examples of learning objects for teaching aritmetics basic.
Keywords: arithmetics basics; arithmetics actions; methods of arithmetics actions; learning objects of arithmetics